Precision analysis of single‐element ultrasound sensor for kinematic analysis of knee joints. Issue 15 (1st July 2014) - Masum, M.A.; Pickering, M.R.; Lambert, A.J.; Scarvell, J.N.; Smith, P.N.
Abstract : Measuring the relative motion of the femur and tibia in a knee joint currently requires tantalum beads to be implanted into the bones. These beads appear as high‐intensity features in radiographs and can be used for precise kinematic measurements. This procedure imposes a strong coupling between accuracy and invasiveness. Advances in ultrasound (US) sensor technology and the availability of micro‐drives mean that it is now possible to construct a small and lightweight US sensor which can be placed on the skin above the tibia and femur. Such a sensor could determine the relative movement of the underlying bone with respect to the sensor. This would then allow the position of the femur and tibia to be measured more accurately than with an optical tracking system that does not take into account the movement of the marker with respect to the bone. For satisfactory performance, the precision of the US sensor should be in the order of 1 mm or less. The experimental results prove that this sub‐millimetre precision is achievable.